Photophysical Investigatigation of Poly [N-isopropylacrylamide-co-Acrylic Acid] Copolymers - Pokhrel, Megh Raj (Journal of Nepal Chemical Society, 2013)
Poly[n-isopropylacrylamide], Poly[NIPAM], and Poly[n-isopropylacrylamide-co-acrylic acid], poly[NIPAM-co-AA] copolymers exhibit the interesting property of size contraction with increasing temperature. Photophysical probe, ruthenium-tris-phenanthroline has been used to monitor the above changes and the studies are correlated with independent study state fluorescence data. DOI: http://dx.doi.org/10.3126/jncs.v28i0.8109 Journal of Nepal Chemical Society Vol. 28, 2011 Page: 67-73 Uploaded Date: May 24, 2013